EZH2 negatively regulates PD-L1 expression in hepatocellular carcinoma. Issue 1 (14th November 2019) - Xiao, Gang; Jin, Li-Lian; Liu, Chao-Qun; Wang, Yong-Chun; Meng, Ya-Ming; Zhou, Zhong-Guo; Chen, Jing; Yu, Xing-Juan; Zhang, Yao-Jun; Xu, Jing; Zheng, Limin
Abstract : Background: Accumulating studies suggest that targeting epigenetic modifications could improve the efficacy of tumor immunotherapy; however, the mechanisms underlying this phenomenon remain largely unknown. Here, we investigated the ability of the epigenetic modifier, enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2), to regulate the expression of immune checkpoint inhibitor, programmed death-1 ligand 1 (PD-L1) in hepatocellular carcinoma (HCC). Methods: Immunohistochemistry and multiplex immunofluorescence staining were performed to analyze the expression and correlation of EZH2 and PD-L1 in HCC tissues. Immunoblotting, quantitative real-time PCR, flow cytometry, chromatin immunoprecipitation, and dual-luciferase reporter gene assays were performed to evaluate the regulatory roles of EZH2 on PD-L1 expression. Results: In vitro cell experiments revealed that EZH2 negatively regulated the PD-L1 expression of hepatoma cell lines in IFNγ-dependent manner. Mechanistic studies demonstrated that EZH2 could suppress PD-L1 expression by upregulating the H3K27me3 levels on the promoters of CD274 (encoding PD-L1) and interferon regulatory factor 1 ( IRF1 ), an essential transcription factor for PD-L1 expression, without affecting the activation of the IFNγ-signal transducer and activator of transcription 1 (STAT1) pathway. Clinical samples from HCC patients with immune-activated microenvironments showed negative correlations between EZH2 and PD-L1 expression in hepatoma cells. Multivariate Cox analysis demonstrated that the combination of EZH2 and PD-L1 was an independent prognostic factor for both OS and RFS for patients with HCC. Conclusions: The epigenetic modificator EZH2 can suppress the expression of immune checkpoint inhibitor PD-L1 by directly upregulating the promoter H3K27me3 levels of CD274 and IRF1 in hepatoma cells, and might serve as a potential therapeutic target for combination of immunotherapy for immune-activated HCC.